Nonsteroidal Antiinflammatory Drugs as Potential Disease‐Modifying Medications in Axial Spondyloarthritis. Issue 4 (24th February 2020) - Wang, Runsheng; Bathon, Joan M.; Ward, Michael M.
Abstract : Nonsteroidal antiinflammatory drugs (NSAIDs) are the first‐line pharmacotherapy for patients with axial spondyloarthritis (SpA). In recent years, treatment options have expanded with the availability of biologic agents, including tumor necrosis factor inhibitors and interleukin‐17 inhibitors. However, a treatment strategy that clearly prevents syndesmophyte formation has not been established. Observational studies of patients with ankylosing spondylitis indicated potential disease‐modifying effects of NSAIDs, but two randomized trials came to different conclusions. More broadly, whether any of the currently available medications for axial SpA have an effect on spine radiographic progression, beyond symptom control, remains inconclusive. In this article, we will review clinical studies of the disease modification effects of NSAIDs and biologics in axial SpA; examine genetic, animal, and clinical evidence of the effects of NSAIDs on bone formation; and discuss how future studies may investigate the question of disease modification in axial SpA.